Breeding of fine quality CMS line Jiazhe A - FU Hao-wei; XUE Qing-zhong (浙江大学学报. 农业与生命科学版, 2001)
Jiazhe A is a WA-type fine quality indica CMS line developed successively through crossing Jiazhe B (No: Y33) to Zhenshan 97A and backcrossing with Jiazhe B as the recurrent parent. It was technically certified in Zhejiang in July 1999. Quality indexes of JiazheA were analyzed and six of ten indexes were fine to meet the first class standards of GB/T 17891-1999, and other four indexes meet the second class standards. The rate of male sterility plant was 100 percent and the sterility degree was 99.98 percent as the result of the technically certify. JiazheA has good characters such as large panicle, early and concentrate anthesis time and high rate of stigma exsertion rate, higher yield in its multiplication and hybrid seed production.